POSITRON EMISION TOMOGRAPHY FOR DETECTION OF DISTANT METASTASES IN PATIENTS WITH BREAST CANCER - N. G. Chanchikova; E. A. Karlova; A. S. Savelyeva; O. A. Silkina; V. I. Chernov; R. V. Zelchan; I. G. Sinilkin; O. D. Bragina; A. A. Medvedeva (Сибирский онкологический журнал, 2020)
Background. Standard imaging techniques, including chest x-ray, ultrasonography, magnetic resonance imaging and computed tomography have some limitations in terms of their ability to detect distant metastases.The purpose of the study was to search for additional diagnostic techniques for breast cancer detection. Material and methods. Results of 18F-FDG PET/scans were retrospectively analyzed in 50 breast cancer patients. Results. Traditional imaging techniques showed suspicion for distant metastases in 29 patients. Of them, metastatic disease was histologically confirmed in 16 patients. Sensitivity and specificity of traditional imaging techniques were 80 % and 67.5 %, respectively. Distant metastases were not detected by 18F-FDG PET/CT in 29 patients, however in one of these patients, both CT and cytological examination performed during the follow-up period revealed pleural metastases. 18F-FDG PET/CT detected distant metastases in 21 patients. Of these patients, two had no evidence of metastases confirmed by biopsy and other diagnostic imaging methods as well as during follow-up period. The sensitivity and specificity of 18F-FDG PET/CT in detection of distant metastases were 95 % and 93.3 %, respectively.Conclusion. Sensitivity of 18F-FDG PET/CT in the detection of breast cancer distant metastasis was significantly higher than that of the traditional imaging techniques.